Negotiating the meaning of female genital mutilation and cutting: A symbolic interactionist approach among religious university students - Hayati, Afita Nur; Wahyuni, Tri; Akhyar, Ramadiva Muhammad; Ahmed, Raya Qahtan; Marjuni, Kamaluddin Nurdin (Islamic Communication Journal, 2025)
The meanings attributed to Female Genital Mutilation/Cutting (FGM/C) are shaped through complex negotiations within religious and socio-cultural frameworks, including those observed in Indonesia. Using a combined qualitative and quantitative (mixed methods)-ethnographic and survey approach, data from 109 students of religious tertiary institutions in East Kalimantan on their perspectives on FGM/C practices can be more comprehensively explored. The results of the study, which were analysed using the three principles of symbolic interactionism, showed that 72.5 per cent of religious college student families still practice FGM/C and 53.2 per cent stated that FGM/C practices are beneficial for women.  However, they are also willing, if asked, to help socialise FGM/C prevention with a percentage of 54.1 percent. This research contributes to revealing the constitutive communication owned by religious tertiary students with the emergence of negotiations on the meaning of FGM/C practices originating from the family environment and from the environment where they pursue higher education. Prevention efforts will have a greater impact when the Government collaborates with the parties according to their contribution. This research contributes to bridging the gap between the traditional understanding that lives in the cultural and religious values of the family and the critical perspective in the academic environment through an inclusive dialogue space to create zero tolerance for the practice of FGM/C, not only in East Kalimantan but also in Indonesia. ***** Pemaknaan seputar praktik Pemotongan dan Pelukaan Genitalia Perempuan (P2GP) terbentuk melalui negosiasi yang kompleks dalam kerangka keagamaan dan sosio-kultural, termasuk yang terjadi di Indonesia. Dengan menggunakan pendekatan gabungan kualitatif dan kuantitatif (mixed methods), data yang berasal dari 109 mahasiswa perguruan tinggi keagamaan di Kalimantan Timur tentang perspektif mereka terhadap praktik P2GP dapat lebih komprehensif dieksplorasi. Hasil penelitian yang dianalisis menggunakan tiga prinsip interaksionisme simbolik menunjukkan sebanyak 72,5 persen keluarga mahasiswa perguruan tinggi keagamaan masih melakukan praktik P2GP dan 53,2 persen menyatakan bahwa praktik P2GP bermanfaat bagi perempuan.  Namun mereka juga bersedia jika diminta untuk membantu sosialisasi pencegahan P2GP dengan prosentase sebesar 54,1 persen. Penelitian ini berkontribusi mengungkap komunikasi konstitutif yang dimiliki oleh mahasiswa perguruan tinggi keagamaan dengan munculnya negosiasi terhadap makna praktik P2GP yang berasal dari lingkungan keluarga dan dari lingkungan tempat mereka menempuh pendidikan tinggi. Upaya pencegahan akan memiliki dampak yang lebih besar ketika Pemerintah berkolaborasi dengan para pihak sesuai dengan kontribusi yang dimiliki. Penelitian ini berkontribusi untuk menjembatani adanya kesenjangan antara pemahaman tradisional yang hidup dalam nilai budaya dan agama keluarga dengan perspektif kritis di lingkungan akademis melalui ruang dialog yang inklusif untuk mewujudkan toleransi nol pada praktik P2GP tidak hanya di Kalimantan Timur tetapi juga di Indonesia.